Benign multicystic mesothelioma with ovarian endometriosis: a rare case report with review of literature - Hota, Basanta Manjari; Bakshi, Kavitha; Movva, Naimisha; Pandirla, Swathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Benign multicystic mesothelioma is a rare pathology that is usually diagnosed on laparotomy for other abdominal diseases. It is more common in females of reproductive age group than in males. The commonest presentation is chronic pain abdomen. Ultrasound is the usual diagnostic tool and the ovarian cyst is the commonest differential diagnosis. Both, reactive and neoplastic hypotheses are considered in the etiopathogenesis of this condition. Management of the disease constitutes complete surgical excision and follow up of the patient. Our patient, a 33 years old parous lady, reported with chronic pain abdomen and right adnexal multiloculated cystic mass. She underwent laparotomy with a provisional diagnosis of ovarian cyst. Histopathology of the excised specimen was benign multicystic mesothelioma with ovarian endometriosis. This case was presented for its rare occurrence, mimicking malignancy, the chance of local recurrence and malignant transformation requiring long term follow up.